pH-responsive magnetic Fe3O4 modified chitosan nanoparticles loaded with β-acids to improve colorectal cancer treatmentStatement of significance - Songlin Guo; Xia Qiao; Lu Ding; Jiayue Liu; Yanan Xu; Jia Cao; Weidong Tian; Duan Ma; Xu Zhang; Bingren Tian (Materials Today Bio)
Oral drug delivery systems designed for antitumor drug administration in colorectal cancer treatment encounter substantial challenges regarding effective delivery, controlled release, and intestinal microbiota homeostasis. In this study, dual-stimulation (pH + magnetic) responsive chitosan nanoparticles (Fe3O4/chitosan (CS)/TPP) loaded with hops β-acids were synthesized for colorectal cancer treatment. In vitro experiments revealed that the fabricated nanoparticles demonstrated sizes ranging from 233 to 381 nm, with zeta potential values exceeding 10 mV. Release studies indicated that β-acids release was pH-dependent. Notably, the β-acids-loaded nanoparticles proved antimicrobial activity through membrane protein interactions. Cell proliferation assays confirmed that these nanoparticles effectively eliminated HCT116 cells while showing minimal toxicity toward NCM460 cells. Following oral administration to mice with in situ colorectal cancer, histopathological evaluation demonstrated that the nanoparticles induced apoptosis at the tumor site, leading to reduced tumor growth. Additionally, the drug-loaded nanoparticles showed enhanced antitumor efficacy compared to free 5-FU. The findings suggest that these nanoparticles significantly increase beneficial bacterial populations while decreasing levels of harmful bacteria. These dual-function nanoparticles, which exhibit both chemotherapeutic and antimicrobial properties, present a promising novel strategy for treating colorectal cancer.